India Hypertension Control Initiative: Blood Pressure Control Using Drug and Dose-Specific Standard Treatment Protocol at Scale in Punjab and Maharashtra, India, 2022 - Prabhdeep Kaur; Manikandanesan Sakthivel; Vettrichelvan Venkatasamy; Padmaja Jogewar; Sandeep S. Gill; Abhishek Kunwar; Meenakshi Sharma; Anupam Khungar Pathni; Kiran Durgad; Swagata Kumar Sahoo; Amol Wankhede; Navneet Kumar; et al. (Ubiquity Press, 2024)
Background: Hypertension treatment coverage is low in India. A stepwise simple treatment protocol is one of the strategies to improve hypertension treatment in primary care. We estimated the effectiveness of various protocol steps to achieve blood pressure (BP) control in public sector health facilities in Punjab and Maharashtra, India, where the India Hypertension Control Initiative (IHCI) was implemented. Methods: We analyzed the records of people enrolled for hypertension treatment and follow-up under IHCI between January 2018 and December 2021 in public sector primary and secondary care facilities across 23 districts from two states. Each state followed a different treatment protocol. We calculated the proportion with controlled BP at each step of the protocol. We also estimated the mean decline in BP pre- and post-treatment. Results: Of 281,209 patients initiated on amlodipine 5 mg, 159,292 continued on protocol drugs and came for a follow-up visit during the first quarter of 2022. Of 33,450 individuals who came for the follow-up in Punjab and 125,842 in Maharashtra, 70% and 76% had controlled BP, respectively, at the first step with amlodipine 5 mg. In Punjab, at the second step with amlodipine 10 mg, the cumulative BP control increased to 75%. A similar 5% (76%-81%) increase was seen in the second step after adding telmisartan 40 mg in Maharashtra. Overall, the mean (SD) systolic blood pressure (SBP) decreased by 16 mmHg from 148 (15) mmHg at the baseline in Punjab. In Maharashtra, the decline in the mean (SD) SBP was about 15 mmHg from the 144 (18) mmHg baseline. Conclusion: Simple drug- and dose-specific protocols helped achieve a high control rate among patients retained in care under program conditions. We recommend treatment protocols starting with a single low-cost drug and escalating with the same or another antihypertensive drug depending on the cost and availability.